Some recent bird observations from Halmahera - Lambert, Frank; Young, Dennis (KUKILA, 1989)
During July 1987, the authors spent 10 days on Halmahera, observing birds in the vicinity of Domato (0 deg 53'N, 127 deg 28'E). Most observations were made 6-10 km inland, in the area known locally as "Batu Puteh". This is an area of steep-sided hills, for the most part forested, but with widespread small scale selective logging of larger hardwoods in all accessible areas. In most of the lower valleys land had been cleared for agriculture, and these areas were usually bordered by degraded forest or scrub. Observations of birds in this area are documented in instances where information is additional to that given in White & Bruce (1986).